(untitled) (Global Journal of Medical Research, 2023)
Abstract Situs inversus totalis is a rare congenital malformation that results in mirror positioning of the thoracic and abdominal organs Situs inversus abdominalis is a right-left inversion limited to the abdomen The association of situs inversus with intestinal band occlusion is very rare We report a case of acute intestinal obstruction associated with situs inversus abdominalis the diagnosis was confirmed by abdominopelvic CT scan and the treatment consisted of a gallbladder resection with anastomosis with good postoperative results Keywords Situs inversus abdominalis Congenital anomaly Intestinal obstruction Surgery